Cutis verticis gyrata secondary to cerebriform intradermal nevus - Olcay Er; Seray Külcü Çakmak; Serra Kayaçetin; Emine Tamer; Ferda Artüz (Our Dermatology Online, 2016)
Cutis vertisis gyrata is a rare skin disease characterized with convoluted folds and furrows formed from thickened skin of the scalp. There are primary and secondary forms of the disease. We report a 22-years-old male patient with cutis verticis gyrata associated with cerebriform intradermal nevus which represents a rare secondary form of the disease.